Methodologies and Intelligent Systems for Technology Enhanced Learning, 8th International Conference - Di Mascio, Tania; Vittorini, Pierpaolo; Gennari, Rosella; De la Prieta, Fernando; Rodríguez, Sara.; Temperini, Marco; Azambuja Silveira, Ricardo; Popescu, Elvira; Lancia, Loreto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the outcomes of the 8th International Conference in Methodologies and Intelligent Systems for Technology Enhanced Learning held in Toledo (Spain) hosted by the University of Castilla-La Mancha from 20 th to 22nd June 2018. Further expanding the topics of the previous editions, the conference provided an open forum for discussing intelligent systems for technology enhanced learning (TEL) and their roots in novel learning theories, empirical methodologies for their design or evaluation, stand-alone and web-based solutions and maker spaces, and also fostering entrepreneurship and increasing business startup ideas. It brought together researchers and developers from industry, the education field and the academic world to report on the latest scientific research, technical advances and methodologies.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence